Isolation and Characterization of Mesenchymal Stem Cells Derived from Different Regions of the Placenta of the Same Donor - Koltsova, A. M.; Zenin, V. V.; Petrosyan, M. A.; Turilova, V. I.; Yakovleva, T. K.; Poljanskaya, G. G. (Cell and tissue biology, 2021)
Two new nonimmortalized cell lines, MSC-PL-1 and MSC-PL-2, were established from different placenta regions of the same donor. Analysis of different characteristics was carried out at early (sixth) and late passages. In the course of long-term cultivation, significant interline differences in growth characteristics and replicative senescence were revealed. Karyotypic analysis showed that, at an early passage, both lines have a normal diploid karyotype with an insignificant number of nonclonal chromosomal rearrangements. MSC-PL-2 cells retain their normal karyotype at the late 15th passage. MSC-PL-1 cultured up to passage 14 in addition to nonclonal rearrangements acquired clonal rearrangements, one of which, X, add (X) (p22.3), was common for MSC-PL-1 cells during replicative senescence. Most cells exhibited high expression of CD44, CD73, CD90, and CD105 surface antigens, vimentin, and HLA-ABC and very low expression of CD34, CD45, and HLA-DR antigens. It was shown that these cells at an early passage have the ability to differentiate in the osteogenic, chondrogenic and adipogenic directions. During the replicative senescence, adipogenic differentiation disappears in MSC-Pl-1 cells, while in the MSC-Pl-2 line, it significantly decreased. Reverse transcription polymerase chain reaction analysis showed a correlation between the level of adipogenic differentiation and the transcriptional activity of the glut4 gene. RT-PCR analysis of nse expression showed a low potency of cells of both lines for neuronal differentiation. It is assumed that the main reason for interline differences lies in the physiological characteristics of the organ region from which the cells were derived.